The Influence of Several Insecticides on Elaeidobius kamerunicus Faust (Coleoptera: Curculionidae) Population in Kalianta Oil Palm Plantation Riau - wahyu syahputra; maryani cyccu tobing; lisnawita lisnawita (Jurnal Agroekoteknologi, 2018)
Elaeidobius kamerunicus is an effective pollinator weevil on oil palm. This reseach was to study the influence of several insecticides on population of E. kamerunicus. This research was conducted at the Indonesian Oil Palm Research Institute (IOPRI) Plantation unit Kalianta Riau from August to September 2016 used Randomized Group Design (RGD) non factorial with 4 kind of active ingredients insecticides, i.e : Delthametrin, Acefat, Lambda Cyhalotrin, and Bacillus thuringiensis with five replications. The results showed that all of insecticide could reduce the population of E. kamerunicus. Population of E. kamerunicus control was higher (1666 adults) than using insecticide. Insecticides that have an effect on decreasing populations of  E. kamerunicus are Delthametrin (1030 adults), Asefat (1209 adults), Lambda Cyhalotrin (1070 adults). E. kamerunicus at the female flowers before treatment (5966 adults) than after treatmen (3987 adults). The appearance of new beetle was not much different for all treatments, its reduced on the non-treated plants (162 insects) compared to post treated plants with active ingredients (108 insects), Asefat (163 insects), Lambda Cyhalotrin (125 insects), dan Bacillus thuringiensis (122 insects).